INVESTIGATING SCHOOL EFFECTIVENESS IN RURAL SETSOTO MUNICIPALITY AREA: A STRATEGY FOR SCHOOL IMPROVEMENT - MOTSOERE, PINKI ANDRIES (Bloemfontein: Central University of Technology, Free State, 2016)
The purpose of this study was to investigate how the schools in rural context in the Setsoto Municipality Area in the Free State Province can improve and maintain their effectiveness. Trends in rural education in developing and developed countries are looked at. Challenges of Principals and teachers most whom have or no training in managing multi-grade teaching in rural context are also explored. The main challenge is that Principals of rural schools have to manage rural schools offering multi-grade teaching and learning despite that few of them have not been trained to manage rural schools, even though rural schools has set of challenges. Despite efforts by Department of Education to improve rural schools effectiveness, rural schools have persistently presented a different set of challenges. This study was aimed at answering the following overarching question: How can schools in rural context improve and maintain their effectiveness? The major findings of this study indicate that there is need for Principals to be trained on how to manage rural schools. After the literature study, empirical research was conducted to investigate good practices and challenges faced by Rural schools principals. Data was collected by means of open and close -ended questionnaire and interviews with five Principals managing rural schools in context. Collected data was analysed using the content analysis framework. However, it was evident through empirical research that some principals are able to manage and improve rural school in context through the consultation and networking with other performing rural schools principals.This study proposes valuable information for rural schools principals ,departmental officials and policy makes and rural schools management: Furthermore, the study will also benefit rural schools teachers in the Setsoto Municipality Area and the whole Country, in terms of school improvement and effectiveness in relation to effective curriculum delivery, teaching and learning
Published Thesis
Keywords: effectiveness; improvement; principals; trained; challenges; maintained; multi-grade teaching; rural school; content analysis framework; rural education; consultation; networking; management